THE EFFECT OF KEGEL EXERCISE ON THE QUALITY OF LIFE IN POST TURP PATIENTS AT MUHAMMADIYAH HOSPITAL - Purwanto, Cucuk Rahmadi; Erniyawati, Yani; Harianto, Susilo; Muhalla, Hafna Ilmy; Okviasanti, Fanni; Wijayanti, Endah Sri (Universitas Airlangga, 2021)
Introduction: Urinary incontinence is a comorbid condition that often occurs in post TURP clients. Low urinary incontinence scores were found in post TURP clients who did Kegel exercises. The purpose of this study was to explain the effect of Kegel exercise on urinary incontinence, and quality of life in post- TURP clients. Methods: The study design was a true experiment pre-post test control group design. The sample size was 32 people who were selected by systematic random sampling, consisting of 16 people in the control group and 16 people in the group treatment. The independent variable in this study was Kegel exercise and the dependent variable was quality of life. Data were collected using a quality of life questionnaire with WHOQOL-BREF. Inferential analysis used statistical t-test (Independent t-Test and Paired t-Test), MANOVA with a significance level of α < 0.05. Results: The results showed that: Kegel exercises improve quality of life scores of the significance level p = 0.045. Conclusion: Kegel exercise can build pubococcygeus muscle mass, improve blood circulation, and improve the bulbocavernosus and ischiocavernosus muscles, thereby reducing urinary incontinence, and quality of life for post TURP clients in a wider population by increasing the reach of the study population and increasing monitoring of client exercise